Characterizing the wheat (Triticum aestivum L.) phosphate transporter gene family and analyzing expression patterns in response to low phosphorus stress during the seedling stage - Song, Meini; Li, Pengcheng; Yao, Lirong; Li, Chengdao; Si, Erjing; Li, Baochun; Meng, Yaxiong; Ma, Xiaole; Yang, Ke; Zhang, Hong; Shang, Xunwu; Wang, Huajun; et al. (Frontiers in Plant Science, 2025)
IntroductionInorganic phosphorus (Pi) is an indispensable nutrient for plant growth, with phosphate transporter proteins (PHTs) having key roles in Pi uptake, transport, and signal transduction in plants. However, a systematic and comprehensive genomic analysis of the wheat PHT family (covering PHT1-5 and PHO1) is lacking.MethodsIn view of this, we successfully identified 180 Triticum aestivum PHT (TaPHT) members in 6 PHT families using bioinformatics, and performed in-depth phylogenetic analyses between these protein sequences and PHT family proteins from Arabidopsis thaliana and an important rice crop.ResultsWe observed that the TaPHT family could be subdivided into 6 phylogenetic clusters, specifically including 46 TaPHT1, 3 TaPHT2, 65 TaPHT3, 22 TaPHT4, 14 TaPHT5, and 30 TaPHO1 members. We also comprehensively profiled the phylogenetic relationships, structural features, conserved motifs, chromosomal localization, cis-acting elements and subcellular localization of these members. These features showed a high degree of conservation within each subfamily. In particular, in the 2000 bp sequence upstream of the TaPHT genes, we identified multiple cis-acting elements closely related to Pi responses, such as P1BS (PHR1 binding site), MBS (MYB binding site), and a W-box (WRKY binding site), which suggested that TaPHT genes were possibly involved in Pi signaling pathways. We screened 24 TaPHT genes by qRT-PCR (real-time quantitative PCR) and investigated their expression in roots and shoots of two wheat cultivars (Pi efficient material SW2 and Pi inefficient material SW14) under low Pi stress conditions. All genes showed up-regulated expression patterns associated with Pi nutritional status, with relative gene expression generally higher in the SW2 cultivar when compared to SW14. Particularly noteworthy was that TaPHT1;36 in the SW2 cultivar showed high and relative stable expression in wheat roots. Combining our bioinformatics and relative gene expression analyses, we preliminarily screened TaPHT1;36 as a candidate gene for low Pi tolerance and further confirmed its subcellular localization.DiscussionOur work not only identified important TaPHT family roles in coping with low Pi stress, but it also provides a functional research basis and candidate gene resource for solving Pi deficiency-related problems.